Art without borders a philosophical exploration of art and humanity - Scharfstein, Ben-Ami 1919- (IG library, 2009)
Ben-Ami Scharfstein draws on neuroscience and psychology to understand the way we both perceive and conceive of art, including its resistance to verbal exposition. Through examples of work by Indian, Chinese, European, African, and Australian artists, "Art Without Borders" probes the distinction between accepting a tradition and defying it through innovation, which leads to a consideration of the notion of artistic genius. Continuing in this comparative vein, Scharfstein examines the mutual influence of European and non-European artists. Then, through a comprehensive evaluation of the world's major art cultures, he shows how all of these individual traditions are gradually, but haltingly, conjoining into a single current of universal art. Finally, he concludes by looking at the ways empathy and intuition can allow members of one culture to appreciate the art of another.